Harnessing Technology: Exploring Elementary School Teacher Education Students’ Perceptions on the Use of Artificial Intelligence - Susanti, Eny Yulia; Emmanuel Kus Eddy Sartono; Banu Setyo Adi; Qazuaini Karim; Endah Marwanti (Mimbar Ilmu, 2025)
The rapid development of artificial intelligence (AI) in education has not been fully matched by digital literacy and the readiness of prospective teachers to integrate it into learning. This study aims to analyze the perceptions of elementary school teacher education students regarding the use of AI in learning. A descriptive quantitative method enriched with qualitative data from semi-structured interviews was employed. The research involved 85 second- and fourth-semester students selected using incidental sampling techniques. Data were collected using a Likert-scale questionnaire for quantitative data, and interviews to deepen survey findings. Quantitative data were analyzed descriptively, while qualitative data were processed using thematic analysis techniques. The results revealed that most students had positive perceptions of AI, particularly in improving learning efficiency, facilitating access to information, and supporting content understanding. However, students also identified risks that need attention, such as the potential for plagiarism, excessive dependency, and a decline in critical thinking and social interaction skills. The study concludes that comprehensive AI literacy is essential for prospective teachers to optimize and responsibly utilize technology. The study recommends integrating AI literacy programs into teacher education curricula and conducting further research on the long-term impacts of AI implementation on learning outcomes in the digital era.